Practice trends in use of morphine for control of intraoperative pain: An audit - Ajai Kumar Jain; Surendra Kumar; Asha Tyagi (Wolters Kluwer Medknow Publications, 2012)
Background: When using morphine as the sole analgesic during conduct of anesthesia, the fear of its adverse postoperative effects primarily sedation and respiratory depression may impede adequate dosing and analgesia. Aim and Objectives: This audit aims to explore the dosing schedules of morphine used during general anesthesia in our institution and to analyze whether the fear of major side effects leads to suboptimal dosing of morphine with inadequate pain relief. Materials and Methods: All subjects scheduled for surgery under general anesthesia wherein morphine was used exclusively for intraoperative analgesia were included in the audit. The audit proforma was completed by the attending anesthesiologist wherein the study period extended from beginning of anesthesia to immediate postoperative period. Result: The study population comprised of 158 patients having mean age 33 ± 14 years and mean weight 52 ± 14 kg. The dose of morphine administered at induction varied widely from 0.05 to 0.3 mg/kg i.v. The VAS (Visual Analogue Scale) score in immediate postoperative period varied from 0 to 10 (mean 1.7 ± 2.0) and sedation score from 1 to 5 (mean 3.94 ± 1.05). Inadequate analgesia with a VAS score ≥4 was seen in 15% patients. Morphine dosage of >0.1 mg/kg was associated with highly significant increase in quality of postoperative analgesia with VAS score <4, and an increase in sedation with sedation score ≤3 (P value < 0.01). However, none of the patients required active intervention for cardiorespiratory support. Conclusion: The practice of dosing morphine in our institution is highly variable with doses ranging from 0.05 to 0.3 mg/kg. This results in inadequate analgesia in 15% patients in postoperative period. Titrating the dose of morphine to expected pain levels inflicted upon by surgical procedures may result in better pain control and less sedated patients postoperatively.